Testing the Principle of Praesumtio Iustae Causa in State Administrative Disputes During Pandemic - Fitriani Sukri, Indah; Rasna, Rasna (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2022)
In the implementation of the state administrative decree, the principle of praesumtio iustae causa is known as part of the implementation of the state administrative decree to resolve state administrative disputes. This principle means that a state administrative decision is always considered valid. This research has the aim of providing protection for the rights of the people that originate from individual rights as well as providing protection for the rights of the community based on the common interests of individuals in the community. The government has an obligation to promote the general welfare as stated in the constitutional mandate. In carrying out this obligation, the government takes regulatory and administrative law enforcement actions. The research method used is descriptive normative research, judging from the effectiveness of this principle is considered valid. And not only that, the possibility of disputes in the state administrative area occurring in the current pandemic era sees this case being included in the area of state administration, even these disputes are often found in the government. The conclusion is Article 65 of Law Number 30 of 2014 concerning Government Administration, what is protected is the interests of the wider community who will be harmed by the issuance of the government decree. So that with the provisions in Article 65 of Law Number 30 of 2014 concerning Government Administration, it can add options for the community to get wider legal protection for the issuance of a government decree/action.